2008
DOI: 10.1177/1043659608322420
|View full text |Cite
|
Sign up to set email alerts
|

Registered Nurses' Attitudes Toward the Protection of Gays and Lesbians in the Workplace

Abstract: This study explores the attitudes of registered nurses toward a nondiscrimination policy in the workplace protective of gays and lesbians and the overall homophobia of nurses. A potential sample of 520 registered nurses licensed in Florida was randomly selected from the state Board of Nursing licensee database. In all, 165 surveys were used in the analysis of the data. Structural equation modeling indicated that support of a nondiscrimination policy protective of gay men and lesbians in the workplace was negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…There is also a responsibility to challenge other nursing colleagues' negative attitudes where they occur (Royal College of Nursing, 2003). Policies and practices that encourage partners to be included in health care planning meetings and decision making are strongly recommended (Blackwell, 2008;Irwin, 2007). Health care professionals engaged in research will need to focus on LGBTIA health care needs and experiences and make recommendations about how these might need to be met more appropriately (Royal College of Nursing, 2003).…”
Section: The Relevance Of Anti-oppressive and Emancipatory Approachesmentioning
confidence: 99%
“…There is also a responsibility to challenge other nursing colleagues' negative attitudes where they occur (Royal College of Nursing, 2003). Policies and practices that encourage partners to be included in health care planning meetings and decision making are strongly recommended (Blackwell, 2008;Irwin, 2007). Health care professionals engaged in research will need to focus on LGBTIA health care needs and experiences and make recommendations about how these might need to be met more appropriately (Royal College of Nursing, 2003).…”
Section: The Relevance Of Anti-oppressive and Emancipatory Approachesmentioning
confidence: 99%
“…2,3,6,12 More positive attitudes and beliefs among CNOs in this study were found to be positively correlated with perceived self-efficacy in advocating for LGBT staff and patients at both personal and professional levels. Although this study's findings are specific to executivelevel nurses, these findings are consistent with findings from other studies on nurses, in general, regarding negative attitudes toward LGBT individuals.…”
Section: Resultsmentioning
confidence: 58%
“…[1][2][3][4][5][6] Homonegativity is a term representing a continuum of discrimination against LGBT people. [1][2][3][4][5][6] Homonegativity is a term representing a continuum of discrimination against LGBT people.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual stereotypes about men in nursing remain prolific (Allison et al , ) and gay and bisexual men nurses are likely to experience negative perceptions and discrimination (Blackwell, ; Harris, ). Harrison () details examples of homophobic violence experienced by gay nurses, as well as examples of nurses ostracized in the workplace and forced to curtail their care because of their sexuality.…”
Section: The Heteronormative Labour Of Caringmentioning
confidence: 99%